Public policy in an uncertain world : analysis and decisions - Manski, Charles F. (Massachusetts : Harvard University Press, 2013)
Failing to account for uncertainty in an uncertain world, policy analysis routinely misleads policy makers with expressions of certitude, this book features an innovation to improve both how policy research is conducted and how it is used by policy makers
Policy analysis -- Policy Decisions
Includes bibliographical references and index.
Keywords: DECISION MAKING